2018
DOI: 10.1094/pbiomes-05-17-0024-r
|View full text |Cite
|
Sign up to set email alerts
|

Cropping History Effects on Pathogen Suppressive and Signaling Dynamics in Streptomyces Communities

Abstract: Diseases remain a yield-limiting factor for crops despite the availability of control measures for many pathogens. Indigenous soil microorganisms can suppress some plant pathogens, yet there is little systematic information on the effects of cropping systems on disease-suppressive populations in soil. Streptomyces have been associated with suppression of plant diseases in several naturally occurring disease-suppressive soils. Pathogen-suppressive activity of Streptomyces communities is correlated with higher b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…From a historical perspective, biocontrol of FWB has been studied for more than 70 years (Thaysen and Butlin, 1945). Studies have reported that disease suppressive sites showed microbial communities displaying higher richness and diversity (Shen et al, 2015b; Köberl et al, 2017), and possibly a higher number of antagonistic members, as observed for streptomycetes (Kinkel et al, 2012; Jauri et al, 2017). Moreover, differences in the composition of these communities correlated with the disease suppressiveness (abundance of Acidobacteria ) or conduciveness (abundance of Bacteroidetes ) of soil (Shen et al, 2015b).…”
Section: Biological Control Agents and Their Modes Of Action: Actual mentioning
confidence: 98%
“…From a historical perspective, biocontrol of FWB has been studied for more than 70 years (Thaysen and Butlin, 1945). Studies have reported that disease suppressive sites showed microbial communities displaying higher richness and diversity (Shen et al, 2015b; Köberl et al, 2017), and possibly a higher number of antagonistic members, as observed for streptomycetes (Kinkel et al, 2012; Jauri et al, 2017). Moreover, differences in the composition of these communities correlated with the disease suppressiveness (abundance of Acidobacteria ) or conduciveness (abundance of Bacteroidetes ) of soil (Shen et al, 2015b).…”
Section: Biological Control Agents and Their Modes Of Action: Actual mentioning
confidence: 98%
“…Microbial diversity is often suggested to be critical for crop productivity (41), where more diverse microbial communities are more resilient to disturbance and are better able to provide ecosystem services such as C and N cycling and disease protection (42,43). Moreover, more diverse cropping histories can significantly enhance soil microbial diversity and plant-beneficial functions (44,45). The greater diversity of bacteria and fungi in both wheat rhizospheres and bulk soils when the soils had a history of CRP participation versus no-till cropping likely reflects the greater diversity of plant communities in the CRP that support more diverse soil communities (46).…”
Section: Figmentioning
confidence: 99%
“…Above that, bacterial interaction networks hypothesized from co-occurrence data were more complex, but those may be differently affected by predation and competition of organisms at higher trophic levels depending on soil conditions and climate. Suppressive bacterial communities were comprised of specific antinobacteria and/or streptomycetes, which is consistent with their antibiotic activities but also production of siderophores enabling better acquisition of iron and other metals 43,44 .…”
Section: Discussionmentioning
confidence: 60%